Analysis of the influence of transition state control strategy on structural load of quad-tiltrotor - HE Yongtao; ZHANG Xiayang; WANG Xin; ZHENG Lixiong (Hangkong gongcheng jinzhan)
There are complex structural load changes in the rotor during the tilt-transition of quad-tiltrotor aircraft,which can directly affect the life of the rotor. The control strategy analysis is beneficial to reveal the influence law of the rotor structural load, which can provide a conclusion basis for the future research on vibration suppression. In order to study the influence of tilt-transition control strategy on rotor dynamic characteristics, a comprehensive flight dynamics model of tiltrotor is established, two typical control strategies of tiltrotor transition state are designed,and the trim characteristics and aerodynamic load characteristics of the fixed tilt angle state are studied through numerical simulation, as well as the influence of the transition state control strategy on the dynamic characteristics of the rotor. By considering the influence of aerodynamics on structure, the aerodynamic loads are treated as external forces applied to the blade surface, and the blade dynamics equation is solved using finite element method. The Newmar k-β method is used to study the displacement response, and the influence of transition state control strategy on the rotor dynamic characteristics is studied. The results show that the periodic variable-pitch control during transition flight can reduce the aerodynamic loads on the rotor, so as to the rotor vibration response, which can achieve the load reduction on the rotor structure.